Handling Technical Reports in the Medical Library - Sargent, Charles W. (1969)
One of the most widely neglected sources of information in the medical library is the technical report. Often this bibliographic form is ignored because there is a general lack of information on the part of the librarian concerning its mysteries. In many cases the technical report provides the most recent and current information on a given subject, and to ignore it or wait for its appearance in the published literature could prove costly to a research project. Technical reports have reached flood proportions since World War II, and are issued from many diverse sources. Means of acquiring, processing, and using the tools which abstract and index this literature are discussed.